Quality of Milk Pasteurized Produced By UD. Gading Mas During Storage in Refrigerator (Faculty of Animal Science Universitas Brawijaya, 2010)
The aim of this research was to study pasteurized milk quality produced by UD. Gading Mas on pH, Acidity, alcohol test and TPC during 5 days storage in refrigerator. On first day showed that weight mass 1,06 (w/w); fat content 2,00 (g/100g), protein content 3,02 (g/100g), Zn 1,67 ppm, Cu<0,005 ppm, Pb 0,02 ppm, As 0,0120 ppm, Hg< 0,0002 ppm, Sn 1,60 ppm dan Cd < 0,001 ppm and organoleptic test included color, flavor and taste were normal. Pasteurized milk characteristic during 5 days refrigeration for pH were 6,57;6,58;6,73;6,60 and 6,50 respectively. Acidity were 1,147 %, 0,145 %, 0,145%, 0,157 %, 0,156 % and 0,175 % respectively. TPC were 6,16 x 101, 1,2. 104; 3,15.104, 0,42.106 and 3,5.108 respectively. It concluded that pasteurized milk produced by UD Gading Mas fulfilled SNI quality standard based on weight mass, pH, acidity, fat, protein, heavy metal content, organoleptic test and TPC. Keywords: pasteurized milk, quality, refrigerator